Studi Islam Berbasis Pendekatan Gender: Kritik dan Rekonstruksi - Retno purwaningsih (CV. ITTC INDONESIA, 2025)
Contemporary Islamic studies face challenges in integrating a just gender perspective. This study critically examines how gender approaches can be used to reconstruct a more inclusive and egalitarian understanding of Islam. Employing qualitative methods with a feminist hermeneutic approach, this research analyzes classical and contemporary religious texts as well as religious practices related to gender issues. The findings reveal that many patriarchal interpretations of Islamic texts are more influenced by socio-cultural contexts than by the substantive values of Islam itself. Gender-based reconstruction of Islamic understanding reveals that the principles of justice ('adl), equality (musawah), and respect for human dignity (karamah insaniyah) are actually aligned with gender equality values. This study concludes that the gender approach in Islamic studies is not merely an analytical method, but also an instrument of liberation to realize Islam as rahmatan lil 'alamin (a mercy to all worlds).